Art markets, agents and collectors : collecting strategies in Europe and the United States, 1550-1950 - Bracken, Susan (Susan Caroline); Turpin, Adriana (Contextualizing art markets., 2021)
"The case studies provided in this manuscript, based on letters and detailed archival research, nuance the history of the art market and the role of the collector within it. Using letters, diaries, account books and other archival sources, the essays show how agents set up networks and acquired works of art, often developing the taste and knowledge of the collectors for whom they were working. They are therefore seen as important actors in the market, having a specific role that separates them from auctioneers, dealers, museum curators or amateurs, while at the same time acknowledging and analyzing the dual positions that many held. Each chronological period is introduced by a contextual essay, written by a leading expert in the field, setting out the art market in the period concerned and the ways in which agents functioned, making it an invaluable tool for those who wish a broader introduction to the intricate workings of the art market"--